Are Banks Different? Evidence from the CDS Market - Burkhard Raunig; Martin Scheicher (Oesterreichische Nationalbank (OeNB), 2009)
This paper uses regression analysis to compare the market pricing of the default risk of banks to that of other firms. We study how CDS traders discriminate between banks and other type of firms and how their judgement changes over time, in particular, since the start of the recent financial turmoil. We use monthly data on the Credit Default Swaps (CDS) of 41 major banks and 162 non-banks. By means of panel analysis, we decompose the CDS premia into the expected loss and the risk premium. Our primary result is that market participants indeed viewed banks differently and that they drastically changed their mind during the recent turmoil that started in August 2007.
Keywords: E43; G12; G13; 330; Credit default swap; market discipline; default risk; risk premium